The effect of sharia supervisory board (DPS), board of directors, and board of commissioners on the financial performance of sharia people financing (BPRS) - Ahmad Fahrurrozi; Muh. Alim Fasieh (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
This study aims to determine the effect of the Sharia Supervisory Board (DPS), the board of directors, and the board of commissioners on the financial performance of BPR Syariah in Sleman Regency 2013-2018. The dependent variable is financial performance proxied by Return on Assets (ROA), while the independent variable is the Sharia Supervisory Board, Board of Directors, and Board of Commissioners. The data analysis technique in this study uses panel data analysis techniques with the Least Square Panel method. The results show that the Sharia Supervisory Board (DPS), the board of directors, and the board of commissioners simultaneously influence the financial performance of BPR Syariah. Then the partial test results show that the Sharia Supervisory Board does not affect the financial performance of Sharia BPRS. At the same time, the Board of Directors has a positive effect on Sharia financial performance, and the Board of Commissioners hurts BPR Syariah.